The DAOA gene is associated with schizophrenia in the Taiwanese population. (June 2017) - Chu, Che-Sheng; Chow, Philip Chik-keung; Cohen-Woods, Sarah; Gaysina, Darya; Tang, Kwong-Yui; McGuffin, Peter
Abstract: The gene D-amino acid oxidase activator ( DAOA ), which has a former name of G72, and the D-amino acid oxidase (DAO) gene have been suggested as candidate genes of schizophrenia. However, association studies have so far yielded equivocal results. We analyzed one single nucleotide polymorphism (SNP) for DAO (rs3741775) and seven SNPs for G72 (rs3916956, rs2391191, rs9558562, rs947267, rs778292, rs3918342, and rs1421292) in this study enrolling 248 schizophrenia cases and 267 controls in the Taiwanese samples. In SNP-based single locus association analyses, the rs778292 in the DAOA gene showed significant association with schizophrenia. The rs3741775 in the DAO gene could not withstand statistically significant after multiple corrections. Additionally, a three-SNP haplotype (rs778292-rs3918342-rs1421292) in the DAOA gene were observed to be significantly associated with schizophrenia. Among them, the TCT haplotype presented higher prevalence in controls than in cases whereas the TTT and CTT haplotype were significantly more frequent in cases than in controls. The study also provides significant evidence for epistatic interactions among DAOA and DAO gene in the development of schizophrenia. These results provide additional evidence and indicate that the DAOA gene and DAOA - DAO gene-gene interactions might play a role for schizophrenia in a Taiwanese sample. Highlights: The SNP rs778292 and a haplotype (rs778292-rs3918342-rs1421292) in the DAOA gene showed significant association with schizophrenia. A haplotype (rs778292-rs3918342-rs1421292) in the DAOA gene were observed to be significantly associated with schizophrenia. The study also provides significant evidence for epistatic interaction between DAOA and DAO gene in the development of schizophrenia in the Taiwanese sample.